HTR4 gene structure and altered expression in the developing lung - Hodge, Emily; Nelson, Carl P.; Miller, Suzanne; Billington, Charlotte K.; Stewart, Ceri E.; Swan, Caroline; Malarstig, Anders; Henry, Amanda P.; Gowland, Catherine; Melén, Erik; Hall, Ian P.; Sayers, Ian (BioMed Central, 2013)
Background: Meta-analyses of genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) spanning the 5-hydroxytryptamine receptor 4 (5-HT4R) gene (HTR4) associated with lung function. The aims of this study were to i) investigate the expression profile of HTR4 in adult and fetal lung tissue and cultured airway cells, ii) further define HTR4 gene structure and iii) explore the potential functional implications of key SNPs using a bioinformatic approach.